Company Tax Coordination cum Tax Rate Competition in the European Union - Wolfgang Eggert; Andreas Haufler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2006)
This paper reviews the recent theoretical literature that analyses the European Unionspolicy to eliminate preferential corporate tax regimes and the proposal to introduce aconsolidated EU tax base with formula apportionment for the taxation of multinationalfirms. Since neither proposal includes a harmonisation of corporate tax rates, a coreissue is how tax competition between member states will be affected by these partialcoordination measures. The conclusions from our review are supportive of the EUs banon preferential tax regimes, but the economic incentive effects of a switch to formulaapportionment are found to be ambiguous.
Keywords: 330; Corporate taxation; tax coordination; multinational firms